2016
DOI: 10.1159/000368550
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function and Cognitive Impairment in People Aged 80 Years and Over with Untreated Hypertension: A Cross-Sectional Survey

Abstract: Background/Aims: Both kidney dysfunction and cognitive impairment are common problems in hypertensive patients. However, few studies have explored the association between these conditions in hypertensive patients aged 80 or over. The current study was undertaken to determine the impact of chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR) on cognitive impairment among an 80-year-old population with untreated hypertension in China. Methods: A total of 395 hypertensive patients aged 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 31 publications
2
16
0
4
Order By: Relevance
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
“…Our findings support previous reports that showed no association between eGFR and cognitive impairment [6,[20][21][22], but contrast to those that did report a significant association [5,9,[23][24][25][26][27][28][29][30]. In addition, other studies also reported significant associations between renal impairment characterised by the presence of microalbuminuria and cognitive impairment [10,20,21,31].…”
Section: Discussionsupporting
confidence: 86%
“…Further, the association of global CI with WMH and cerebral atrophy was independent of CVD history and CVD risk factors for the whole CKD group. These findings might be supported by previous studies indicating that CKD, per se, contributes to cognitive decline [36], independent of ischemic cerebral lesions [35], and that HD is associated with CI, independent of CVD risk factors, SVI, and brain atrophy [37]. Indeed, white matter lesions, which were shown to be a strong predictor of general CI in our study, could be present not only in stroke but also in multiple sclerosis [38], pyridoxine deficiency, and cerebral metabolic disturbances in CKD patients [18].…”
Section: Discussionsupporting
confidence: 89%
“…Nove artigos abordavam problemas cardíacos (David, Mello, Bruscato, & Moriguchi, 2016;Gomes, et al, 2016;Ho, 2014;Luo, et al, 2014;Pérez-Orcero, et al, 2016;Ragot, Sosner, Dievart, & Herpin, 2014;Rossi, et al, 2016;Wang, et al, 2016;Warwick, et al, 2015), incluindo dados hemodinâmicos e antropométricos como procedimentos a serem utilizados no controle de algumas patologias como hipertensão e outras. Reitera-se a ênfase dos pesquisadores sobre investigações relacionadas aos agravos mais frequentes na saúde do idoso longevo e respectivas terapêuticas.…”
Section: Digestive and Liver Diseaseunclassified
“…Quanto ao método de coleta de dados utilizado nos estudos pesquisados, verificamos uma grande diversidade de instrumentos (31 tipos diferentes). Os instrumentos mais encontrados nesta revisão relacionaram-se à avaliação funcional, em nove artigos (Bonicoli, et al, 2016;Downer, Chen, Wong, & Markides, 2016;Hegendörfer, et al, 2017b;Levinson, et al, 2016;Pego, Nunes, Ferreira, Sousa, & Amaral-Silva,, 2016;Wang, et al, 2016;Warwick, et al, 2015;Yoshida, et al, 2017;Yu, et al, 2017) e instrumentos preditores de risco, em sete artigos (Hegendörfer, et al, 2017b;Levinson, et al, 2016;Luo, et al, 2014;Mione, et al, 2016;Pego, Nunes, Ferreira, Sousa, & Amaral-Silva, 2016;Rinaldi, et al, 2017;Yoshida, et al, 2017). Para Paixão (2005), a definição da avaliação do estado funcional seria "o nível com o qual a pessoa desempenha funções e atividades da vida diária".…”
Section: Digestive and Liver Diseaseunclassified
See 1 more Smart Citation